The Triadic Contours of Ethics in Practice-Based and Interdisciplinary Research - Hansen, Pil (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2023)
In this forum article, I begin to contour the triad of partly overlapping ethical spheres that I operate within when crossing practice-based and empirical research in the performing arts. I also begin to suggest a few approaches that may help me and others navigate these spheres. The ethical spheres I contour are (1) situational and relational ethics; (2) equity, diversity, inclusivity, and accessibility (EDIA); and (3) institutional ethics protocols. This triad is, furthermore, considered with reference to an ethically complex research program titled “strengths-based dramaturgies of accessibility in the performing arts.”